The best way to bury your husband - Casale, Alexia (Penguin Books, 2024)
After killing her husband-a truly terrible man, Sally finds herself leading an extremely unusual self-help group of women who have come together to heal the damage their husbands have done-and to work out a plan to get rid of the bodies and get away with it.